Erythrocyte Index Profile As An Indication of Anemia Based On Morphology In Patients (Tuberculosis) Undergoing Treatment - Aini, Aini; Saptiana, Baiq Agustin; Pauzan, Pauzan; Mentari, Ika Nurfajri (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacteria which usually attacks the lungs but can also attack other organs such as lymph nodes, heart and so on. Tuberculosis is transmitted through the air, from one person to another, usually through the sputum droplets of someone who has had TB. Anaemia in Tuberculosis can be caused by disruption of the erythropoiesis process by inflammatory mediators, shortening of the life span of erythrocytes, impaired iron metabolism, malabsorption, and inadequate nutrition due to low appetite. The research method used is descriptive. Where this study will describe how the erythrocyte index is in tuberculosis patients who take medication for 1 month, 2 months, 3 months, 4 months, 5 months, and 6 months of treatment. The total respondents in this study were 20 respondents, including 10 men and 10 women. Based on the results of the erythrocyte index count, the type of erythrocytes shows the number of respondents with Hypochromic Microcytic anaemia as many as 6 people, Normochromic Microcytic anaemia as many as 3 people, Hypochromic Normocytic anaemia 1 person and Normochromic Normocytic anaemia as many as 10 people.